Online political participation, online contacts with out-groups members and social distances. Issue 1 (2nd January 2017) - Lissitsa, Sabina
ABSTRACT: In light of the growing role of social media in conflict management, the current study analyzes the interrelationship of online political participation of Israeli Jews, the frequency of their online contacts with Arabs, and Jews' perceived social distances from Arabs. The research was conducted through an online survey of a representative sample of 458 Israeli Jews who use the social media at least 3 times a week. Overall, although causation cannot be inferred because of the correlational design of our study, results suggest that frequency of online contacts may positively affect closeness to Arabs in line with contact theory. In keeping with the socialization perspective of political engagement, the findings indicate that the impact of online political participation on social distances from Arabs was mediated by interactions between Jews and Arabs in the social media.